Limited contribution of NR5A1 (SF-1) mutations in women with primary ovarian insufficiency (POI) - Janse, Femi; de With, Larissa M.; Duran, Karen J.; Kloosterman, Wigard P.; Goverde, Angelique J.; Lambalk, Cornelius B.; Laven, Joop S.E.; Fauser, Bart C.J.M.; Giltay, Jacques C. (Fertility and sterility, 2012)
To evaluate the significance of NR5A1 mutations in a large, well-phenotyped cohort of women with primary ovarian insufficiency (POI). Mutations in the NR5A1 gene (SF-1) were previously described in disorders of sexual development and adrenal insufficiency. Recently, a high frequency of NR5A1 gene mutations was reported in a small group of women with POI. Cross-sectional cohort study. University hospital. Well-phenotyped women (n = 386) with secondary amenorrhea and diagnosed with POI, including women with familial POI (n = 77). None. The entire coding region and splice sites of the NR5A1 gene were PCR-amplified and sequenced. The pathogenicity of identified mutations was predicted in silico by assessing Align-GVGD class and Grantham score. Sequencing was successful in 356 patients with POI. In total, 9 mutations were identified in 10 patients. Five of these mutations concerned novel nonconservative mutations occurring in 5 patients. Prediction of effect on protein function showed low to intermediate pathogenicity for all nonconservative mutations. The overall NR5A1 gene mutation rate was 1.4%. The current study demonstrates that mutations in the NR5A1 gene are rare in women with POI. Primary ovarian insufficiency remains unexplained in the great majority of patients; therefore, continued efforts are needed to elucidate its underlying genetic factors.